2014
DOI: 10.1186/1471-2164-15-12
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of DNA methylation in bovine placentas

Abstract: BackgroundDNA methylation is an important epigenetic modification that is essential for epigenetic gene regulation in development and disease. To date, the genome-wide DNA methylation maps of many organisms have been reported, but the methylation pattern of cattle remains unknown.ResultsWe showed the genome-wide DNA methylation map in placental tissues using methylated DNA immunoprecipitation combined with high-throughput sequencing (MeDIP-seq). In cattle, the methylation levels in the gene body are relatively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
63
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(83 citation statements)
references
References 52 publications
17
63
0
3
Order By: Relevance
“…In the present study, CpG islands showed a higher methylation density compared with previous studies in other species. Recent works on horse, cattle and chicken epigenomes found 10 to 20% of methylated CGIs across the genomes [14, 16, 17]. The results in the present work indicate that almost 50% of the CGIs in goat are methylated in hypothalamus and ovary.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…In the present study, CpG islands showed a higher methylation density compared with previous studies in other species. Recent works on horse, cattle and chicken epigenomes found 10 to 20% of methylated CGIs across the genomes [14, 16, 17]. The results in the present work indicate that almost 50% of the CGIs in goat are methylated in hypothalamus and ovary.…”
Section: Discussionsupporting
confidence: 65%
“…comparing the DNA methylation distribution pattern in goat to that found in bovine placenta and horse [14, 17]. In bovine placenta, the DNA methylation level decreased before the TSS, noticeably increases in intragenic regions, and is constantly low downstream of genes.…”
Section: Discussionmentioning
confidence: 99%
“…These results specified that most CGIs are unmethylated. In the study of Su et al (2014) in cattle, 20.12% of CGIs were methylated, which could be probably due to the different approaches used to detect CGIs. When comparing the status of methylated CGIs investigated in different regions of the genome, most of the methylated CGIs were present in the introns, intergenic and CDS regions and the lowest number of the methylated CGIs existed in the promoter regions (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…To assess the methylation status of CpG islands, the MeDIP-seq methylation data of placental tissue downloaded from Su et al (2014) study was used. Here, highly methylated regions (HMRs), which are also called peaks, were used to evaluate the methylation status in CGIs.…”
Section: Methodsmentioning
confidence: 99%
“…The production of clones from an adult somatic cell is enabled by the capacity of the oocyte to reprogramme the epigenome of a differentiated nucleus to totipotency, and aberrant epigenetic reprogramming is recognized as one of the leading causes of the developmental abnormalities encountered in clones4. Accordingly, DNA methylation defects have been reported in bovine clones, at both the global level56 and at candidate loci789, but genome-wide views of the affected regions are still scarce10 and associations with phenotypic anomalies have not been clearly demonstrated.…”
mentioning
confidence: 99%